2016
DOI: 10.3238/arztebl.2016.0816
|View full text |Cite
|
Sign up to set email alerts
|

The prevention and treatment of retinal complications in diabetes

Abstract: Regular, risk-adapted ophthalmological examinations, with standardized documentation of the findings for communication between ophthalmologists and the patients' treating primary care physicians/diabetologists, is essential for the prevention of diabetic retinal complications, and for their optimal treatment if they are already present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 44 publications
(14 reference statements)
0
23
0
19
Order By: Relevance
“…Eine Zusammenfassung der abgefragten Aussagen und Zustimmungswerte der Umfrageteilnehmer findet sich in ▶ Tab. 4.…”
Section: Der Einsatz Von Dex-implantat In Kombination Mit Anderen Theunclassified
See 3 more Smart Citations
“…Eine Zusammenfassung der abgefragten Aussagen und Zustimmungswerte der Umfrageteilnehmer findet sich in ▶ Tab. 4.…”
Section: Der Einsatz Von Dex-implantat In Kombination Mit Anderen Theunclassified
“…In der aktuellsten deutschen Empfehlung ist das DEX-Implantat ausschließlich als Mittel der zweiten Wahl eingestuft. Als Grundlage dienten hier nur die Ergebnisse der Zulassungsstudien [4,16].…”
Section: Diskussionunclassified
See 2 more Smart Citations
“…There is no doubt that glycemic control plays the most momentous role in management of DN; keeping blood glucose within normal limits is a foundation and prerequisite for the treatment of DN [32]. Several studies have indicated that a close relationship has been established between poor glycemic control and microvascular complications, including DN [33].…”
Section: Prevention and Management Of Dnmentioning
confidence: 99%